2013
DOI: 10.11648/j.ijmsa.20130206.12
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Relaxation, Ionic Conduction and Complex Impedance Studies on NaNo3 Fast Ion Conductor

Abstract: AC conductivity, dielectric constant, loss and electric modulus of Sodium nitrate system have been studied in the frequency range from 1Hz to 10MHz and in the temperature range from 303 K to 563 K by employing impedance spectroscopy. The frequency dependent ac conductivity follows Jonscher's universal power law. Dimensionless frequency exponent (n), dispersion parameter (A) are determined. The change over frequency independent conductivity to frequency dependent conductivity at all temperatures shows the relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
1
9
0
1
Order By: Relevance
“…Moreover, Jonscher's universal relaxation law for dielectrics generally refers to displacement current J(t), whereas the position <x(t)> = xo t -n for a charged domain wall should contribute <dx(t)/dt> = xo t -n-1 to such currents, worsening the agreement in the present case. However, it is known [70][71][72] However, domain relaxations on a time scale of 20 hours, as in the present study, were reported [74][75][76][77] in 2014 with 50% decay reached in a few thousand seconds, as in our data. Very low (sub-Hz) frequency dielectric studies imply that these long relaxation times involve oxygen vacancy motion.…”
Section: Period Doublingsupporting
confidence: 72%
“…Moreover, Jonscher's universal relaxation law for dielectrics generally refers to displacement current J(t), whereas the position <x(t)> = xo t -n for a charged domain wall should contribute <dx(t)/dt> = xo t -n-1 to such currents, worsening the agreement in the present case. However, it is known [70][71][72] However, domain relaxations on a time scale of 20 hours, as in the present study, were reported [74][75][76][77] in 2014 with 50% decay reached in a few thousand seconds, as in our data. Very low (sub-Hz) frequency dielectric studies imply that these long relaxation times involve oxygen vacancy motion.…”
Section: Period Doublingsupporting
confidence: 72%
“…, it is observed that the dielectric constant ε slowly decreases with increase in applied frequency f. This can be explained on the basis of oscillation of free dipoles in presence of alternating field. At very low frequencies (f << 1/τ, τ is the relaxation time), dipoles follow the electric field, while at very high frequencies (f >> 1/τ) dipoles begin to lag behind the field and ε slightly decreases 42,44 . It is also reported that the higher values of ε at low frequencies is due to space charge polarization or accumulation of charges at interfaces of sample and electrode 44 .…”
Section: 35kbtmentioning
confidence: 99%
“…Untuk bagian riil kurva permittivitas, fenomena pada frekuensi rendah ini merupakan hasil kontribusi kuat dari akumulasi muatan pada daerah antar muka elektrolit dan elektroda [27], sedangkan untuk kurva rugi dielektrik merupakan akibat dari perpindahan ion di dalam material [28], seperti yang digambarkan sebagai ekor pada ujung kurva impedansi pada Gambar 3. Nilai permittivitas tersebut kemudian diikuti oleh daerah yang hampir tidak bergantung frekuensi pada daerah frekuensi lebih tinggi, yang diakibatkan oleh pembalikan medan listrik secara periodik dan cepat, yang mengakibatkan tidak ada lagi difusi dan vibrasi ion yang tersisa pada daerah frekuensi tersebut [29].…”
Section: Pendahuluanunclassified